초고경도 Ti–Al–Si–N 나노복합체 코팅막의 미세구조 및 트라이볼로지 거동에 관한 연구 - 허성보(Sung-Bo Heo); 김왕렬(Wang Ryeol Kim) (Biuletyn Uniejowski, 2021)
In this study, the influence of silicon contents on the microstructure, mechanical and tribological properties of Ti-Al-Si-N coatings were systematically investigated for application of cutting tools. The composition of the Ti-Al-Si-N coatings were controlled by different combinations of TiAl2 and Ti4Si composite target powers using an arc ion plating technique in a reactive gas mixture of high purity Ar and N2 during depositions. Ti-Al-Si-N films were nanocomposite consisting of nanosized (Ti,Al,Si)N crystallites embedded in an amorphous Si3N4/SiO2 matrix. The instrumental analyses revealed that the synthesized Ti-Al-Si-N film with Si content of 5.63 at.% was a nanocomposites consisting of nano-sized crystallites (5-7 nm in dia.) and a three dimensional thin layer of amorphous Si3N4 phase. The hardness of the Ti-Al-Si-N coatings also exhibited the maximum hardness value of about 47 GPa at a silicon content of ~5.63 at.% due to the microstructural change to a nanocomposite as well as the solid-solution hardening. The coating has a low friction coefficient of 0.55 at room temperature against an Inconel alloy ball. These excellent mechanical and tribological properties of the Ti-Al-Si-N coatings could help to improve the performance of machining and cutting tool applications.